Pengaruh Penghindaran Pajak terhadap Risiko Penurunan Harga Saham dengan Kinerja Keberlanjutan sebagai Variabel Moderasi - Mutia Arum Arsita; Dahlia Sari (Owner : Riset dan Jurnal Akuntansi, 2026)
Negative news concerning a company often incentivizes its managers to sell their shares due to a loss of market confidence and pressure. Large-scale, synchronized share selling can potentially cause the stock price to decline further, resulting in a stock price crash risk driven by negative market sentiment. The purpose of this study is to analyze the effect of tax avoidance on stock price crash risk and to examine whether the moderation of sustainability performance (ESG) influences this relationship, addressing a current research gap in the literature. Method: The data utilized in this research consists of non-financial firms listed on the Indonesia Stock Exchange (IDX) over the period 2018 to 2023. Data was primarily sourced from Thomson Reuters. Due to the nature of the data, the study employed unbalanced panel data, resulting in a final sample of 156 firm-year observations. The hypothesis testing was conducted using the Fixed Effect Model (FEM) panel data regression. Result: The empirical results indicate that tax avoidance is not significantly related to stock price crash risk. Furthermore, the moderation of sustainability disclosure is not proven to affect the relationship between tax avoidance and stock price crash risk. Discussion: This study provides the first empirical evidence from Indonesia combining and testing the relationship among tax avoidance, ESG performance, and stock price crash risk. The lack of significant findings suggests that sustainability disclosure in the Indonesian context may not yet serve as a credible signal for investors to effectively mitigate the risks of information opacity associated with tax avoidance practices.